Legal Certainty for Creditors Due to Legal Efforts to Postpone Debtors' Debt Payment Obligations - Sodikin Sodikin; Roosdiana Harahap (Gudang Jurnal Multidisiplin Ilmu, 2026)
The Suspension of Debt Payment Obligations (PKPU) is a legal procedure that allows debtors who are unable, or expect to be unable, to continue paying their due and collectible debts to seek legal recourse. Debtors in such situations can initiate legal action during the PKPU process. However, the question arises: what is the legal certainty for creditors following the Constitutional Court's decision that encourages debtors to pursue legal action? This study uses a descriptive normative research method to analyze the legal issues related to such actions. The findings indicate that the legal recourse available to debtors in specific circumstances significantly impacts creditors. This leads to uncertainties regarding payment, especially if the debtor decides to file for legal action. Additionally, these uncertainties can affect the creditor's business operations. The Constitutional Court's decision, subsequently reinforced by a Circular Letter from the Supreme Court, does not adequately address the gaps in legal certainty faced by creditors. This situation complicates creditors' efforts to secure their rights, which are the obligations of the debtor.